Human's Capability to Discriminate Spatial Forces at the Big Toe - Hagengruber, Annette; Höppner, Hannes; Vogel, Jörn (Frontiers in Neurorobotics, 2018)
A key factor for reliable object manipulation is the tactile information provided by the skin of our hands. As this sensory information is so essential in our daily life it should also be provided during teleoperation of robotic devices or in the control of myoelectric prosthesis. It is well known that feeding back the tactile information to the user can lead to a more natural and intuitive control over robotic devices. However, in some applications it is difficult to use the hands as natural feedback channel since they may already be overloaded with other tasks, or e.g. in case of hand prosthesis not accessible at all. Many alternatives for tactile feedback to the human hand have already been investigated. In particular, one approach shows that humans can integrate uni-directional (normal) force feedback at the toe into their sensorimotor-control loop. Extending this work, we investigate the human’s capability to discriminate spatial forces at the bare front side of their toe. A state-of-the-art haptic feedback device was used to apply forces with three different amplitudes--–2N, 5N, and 8N---to subjects' right big toe. During the experiments, different force stimuli were presented, i.e. the direction of the applied force was changed, such that tangential components were evident. In total the four directions up (distal), down (proximal), left (medial), and right (lateral) were tested. The proportion of the tangential force was varied according to a directional change of 5° to 25° degrees with respect to the normal force. Given these force stimuli, the subjects’ task was to identify the directional force-changes. We found the amplitude of the force as well as the proportion of tangential forces having a significant influence on the success rate. Further showed the direction right a significant difference to the other directions. The stimuli with a force amplitude of 8N achieved success rates over 89% in all directions. The results of the user study provide evidence that the subjects were able to discriminate spatial forces at their toe within defined force amplitudes and tangential proportion.